Vesicular Ganglioside GM1 From Breast Tumor Cells Stimulated Epithelial-to-Mesenchymal Transition of Recipient MCF-10A Cells - Ma, Qilong; Zhuo, Dinghao; Guan, Feng; Li, Xiang; Yang, Xiaomin; Tan, Zengqi (Frontiers in Oncology, 2022)
Small extracellular vesicle (sEV) is a kind of membrane structure secreted by cells, which is involved in physiological and pathological processes by participating in intercellular communication. Glycosphingolipids (GSLs) are enriched in sEV and can be delivered to recipient cells. In this study, we found that overexpression of B3GALT4, the glycosyltransferase responsible for ganglioside GM1 synthesis, can induce the epithelial-mesenchymal transition (EMT) process in MCF-10A cells. Moreover, GM1 was verified to be presented on sEV from breast cancer cells. Overexpression of B3GALT4 resulted in elevated vesicular GM1 levels and increased sEV secretion in breast cancer cells. Proteomic analysis revealed that eleven sEV secretion-related proteins were differentially expressed, which might contribute to the altered sEV secretion. Of the identified proteins, 15 oncogenic differentially expressed proteins were documented to be presented in sEV. With the treatment of GM1 enriched sEV from breast cancer cells, the EMT process was induced in recipient non-tumorigenic epithelial MCF-10A cells. Our findings demonstrated that GM1 enriched sEV derived from breast cancer cells induced the EMT process of recipient cells, which might provide an essential information for the deep insight of the biological function of vesicular GM1.